2023
DOI: 10.1017/s0963180123000245
|View full text |Cite
|
Sign up to set email alerts
|

Minding Rights: Mapping Ethical and Legal Foundations of ‘Neurorights’

Abstract: The rise of neurotechnologies, especially in combination with artificial intelligence (AI)-based methods for brain data analytics, has given rise to concerns around the protection of mental privacy, mental integrity and cognitive liberty – often framed as “neurorights” in ethical, legal, and policy discussions. Several states are now looking at including neurorights into their constitutional legal frameworks, and international institutions and organizations, such as UNESCO and the Council of Europe, are taking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 63 publications
0
12
0
6
Order By: Relevance
“…As underlined by the Girardi /Emotive Inc. judgment, “the development of new technologies involves more and more aspects of the human person—aspects that were unthinkable a few years ago.” The State is expected to act “in order to prevent and anticipate their possible effects, in addition to directly protecting human integrity in its totality, including privacy and confidentiality” (see paragraph 8 of the judgment). Therefore, the judgment points out that privacy is an (important) aspect of human integrity, or, in other words, of dignity and other human rights as cognitive liberty, freedom of thought and identity ( Andorno, 2023 ; Farahany, 2023 ; Lavazza and Giorgi, 2023 ; Ligtharts et al, 2023 ).…”
Section: Protection Of Neurodata As a Protection Of Human Rightsmentioning
confidence: 99%
See 1 more Smart Citation
“…As underlined by the Girardi /Emotive Inc. judgment, “the development of new technologies involves more and more aspects of the human person—aspects that were unthinkable a few years ago.” The State is expected to act “in order to prevent and anticipate their possible effects, in addition to directly protecting human integrity in its totality, including privacy and confidentiality” (see paragraph 8 of the judgment). Therefore, the judgment points out that privacy is an (important) aspect of human integrity, or, in other words, of dignity and other human rights as cognitive liberty, freedom of thought and identity ( Andorno, 2023 ; Farahany, 2023 ; Lavazza and Giorgi, 2023 ; Ligtharts et al, 2023 ).…”
Section: Protection Of Neurodata As a Protection Of Human Rightsmentioning
confidence: 99%
“…Neurodata can affect mental integrity because, among other things, it can "control mental states, decode them by providing behavioral information... " (Zohny et al, 2023). For its part (Ligtharts et al, 2023) establishes the possibility that "thoughts and feelings can be observed, not only indirectly through behavior, but also through multimodal data analysis, in which data on brain states play an (Zohny et al, 2023). "Decoding brain data may 1 day reveal mental information," so neurodata affects not only mental privacy but also mental integrity.…”
Section: The "Neurorights" Within Chilean Lawmentioning
confidence: 99%
“…The future application of neurotechnology in criminal justice raises a range of new legal questions [10]. The most fundamental concerns exist vis-avis protection of human rights, as recently underscored by UNESCO and the United Nations Human Rights Council (A/HRC/RES/51/3) [11]. Human rights are protected by national constitutions, but also through international treaties such as the Universal Declaration of Human Rights and the European Convention on Human Rights.…”
Section: Requirements Concerning the Protection Of Human Rightsmentioning
confidence: 99%
“…Other human rights, such as the right to freedom of thought and mental privacy, are also relevant and much is still unclear about the human rights issues attached to the application of neurotechnology in criminal justice [10,11]. These issues, as well as topics such as data protection, have to receive careful attention before neurotechnology can be applied in a criminal justice setting.…”
Section: Requirements Concerning the Protection Of Human Rightsmentioning
confidence: 99%
“…If a country strictly regulates the use of neurotechnologies, could this limit scientific and technological progress to improve people's lives? The debate is still open, and there are many active authors providing a deeper insight into all the different positions (for an updated review on the topic, see Ligthart et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%